2021
DOI: 10.3389/fgene.2021.649387
|View full text |Cite
|
Sign up to set email alerts
|

CCN Family Proteins in Cancer: Insight Into Their Structures and Coordination Role in Tumor Microenvironment

Abstract: The crosstalk between tumor cells and the tumor microenvironment (TME), triggers a variety of critical signaling pathways and promotes the malignant progression of cancer. The success rate of cancer therapy through targeting single molecule of this crosstalk may be extremely low, whereas co-targeting multiple components could be complicated design and likely to have more side effects. The six members of cellular communication network (CCN) family proteins are scaffolding proteins that may govern the TME, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 152 publications
2
21
0
Order By: Relevance
“…Currently, the tumor microenvironment (TME) makes a significant impact on malignancies ( Bi et al, 2020 ; Jia et al, 2021 ; Li et al, 2021 ). As a major component of TME, CAF has multiple pro-tumorigenic functions during tumorigenesis ( Yang W et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the tumor microenvironment (TME) makes a significant impact on malignancies ( Bi et al, 2020 ; Jia et al, 2021 ; Li et al, 2021 ). As a major component of TME, CAF has multiple pro-tumorigenic functions during tumorigenesis ( Yang W et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The six different members of the CCN gene family includes Cyr61 (CCN1), CTGF (CCN2), NOV (CCN3), WISP-1 (CCN4), WISP-2 (CCN5), and WISP-3 (CCN6) [ 24 ]. Biological functions, such as cell growth, ECM regulation, cell adhesion, migration, wound healing and angiogenesis, and diseases including fibrosis, cancer and vascular diseases are mostly regulated by the expression of the CCN gene family.…”
Section: Ccn Gene Familymentioning
confidence: 99%
“…The CCN family proteins contain six members that may regulate the tumor microenvironment. Numerous studies have suggested CCN family proteins can be an effective target in treating breast cancer (see Figure 2 ) [ 24 ].…”
Section: Pharmacological Advances In Treating Breast Cancer By Targeting Ccn Proteinsmentioning
confidence: 99%
“…CCN3/NOV is also known for promoting angiogenesis by supporting endothelial cell migration, adhesion, and survival [ 31 ]. CCN4/WISP-1 and CCN5/WISP-2 have roles in metabolic disorders involving glucose homeostasis, such as insulin resistance, diabetes, and obesity [ 16 , 32 , 33 ], and have been associated with the development and regulation of different types of cancers [ 34 , 35 , 36 ]. CCN6/WISP-3, on the other hand, has been shown to work as a tumor suppressor blocking breast cancer development [ 37 , 38 , 39 ].…”
Section: The Ccn Family Of Matricellular Proteinsmentioning
confidence: 99%